High-Precision Automotive Radar Target Simulation - Diewald, Axel (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2023)
Radar target simulators (RTSs) deceive a radar under test (RuT) by creating an artificial environment consisting of virtual radar targets. In this work, new techniques are presented that overcome the rasterization deficiency of current RTS systems and enable the generation of virtual targets at arbitrary high-precision positions. This allows for continuous movement of the targets and thus a more credible simulation environment.